ANALISIS PENGARUH MOTIVASI, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Triyanto, Arif; Suddin, Alwi; Suprayitno, Suprayitno (Universitas Slamet Riyadi, 2019)
The purpose of this study was to analyze the significance of motivation, compensation and work discipline on employee performance and analyze the independent variables that had the dominant influence on employee performance. This type of research is a survey of UNISRI Surakarta staff. The research population is the UNISRI Surakarta company. The sampling technique uses proportional cluster random sampling with a sample of 70 people. The technique of collecting data using questionnaires and interviews. The data analysis technique uses multiple linear regression. The results of this study indicate that motivation is not significant for employee performance. Significant compensation for employee performance. Significant work discipline on employee performance. Work discipline is the most dominant variable influencing employee performance.